2022
DOI: 10.2991/assehr.k.220706.135
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis and Communicative Effect on Neologisms During Covid-19 Pandemic

Abstract: Neologisms in linguistics refer to words or phrases that have recently been created or invented or given new meanings to existing words based on specific social and cultural backgrounds, which shows the vitality and creativity of language to some extent. In today's world, Covid-19 has undoubtedly become a hot issue of global concern in recent years, and new words have come into being. During the Covid-19 pandemic, neologisms mostly appear in the form of nouns, adjectives and verbs, and they all involve common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…These researches explored neologisms from different categories, e.g., social media, magazines, gay language, and periods, i.e., the global pandemic. Studies by Amiruddin (2022), Kang (2022), and Akut (2020) analyzed neologisms that emerged during the coronavirus pandemic by focusing on their morphological structures and processes. These studies revealed that most of these words are nouns and verbs and were created using compounding, blending, and affixation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These researches explored neologisms from different categories, e.g., social media, magazines, gay language, and periods, i.e., the global pandemic. Studies by Amiruddin (2022), Kang (2022), and Akut (2020) analyzed neologisms that emerged during the coronavirus pandemic by focusing on their morphological structures and processes. These studies revealed that most of these words are nouns and verbs and were created using compounding, blending, and affixation.…”
Section: Literature Reviewmentioning
confidence: 99%